The Validity and Reliability of the PLC Module in PLC Programming and Applications Topics - Nurul Azimah Ahmad Arzaai; Mat Nashir, Irdayanti; Yusoff, Saiful Adli (Emerging Advances in Integrated Technology, 2026)
The advancement of technical and vocational education requires the integration of effective teaching aids that support both theoretical understanding and practical skills. The purpose of this study is to evaluate the validity and reliability of the PLC Module in PLC programming and applications topics. A total of seven experts in Programmable Logic Controller (PLC) from various institutions and industry reviewed the module's content validity. A pilot study was conducted with 30 polytechnic students who engaged in all activities outlined in the PLC Module to evaluate its reliability. This phase was followed by an assessment of the students' feedback using a module reliability questionnaire. The findings show that the developed module has high validity with a content validity coefficient of 0.92 and excellent reliability with a Cronbach's alpha value of 0.98. These results indicate that the PLC Module PLC programming and application topics are suitable for use. Additionally, feedback from both experts and students will be used to further refine the content, ensuring the developed module can meet the objectives and can be implemented. Furthermore, these findings have significant implications for the teaching and learning of PLC, specifically PLC programming and applications topics, whereas the PLC Module can serve as a valuable resource for educators and students in this field.